STRATEGI PERCEPATAN PEMBANGUNAN DAERAH BERBASIS KEARIFAN LOKAL DI KECAMATAN GUNUNG WUNGKAL - Lailatis Syarifah (UIN Sunan Kalijaga Yogyakarta, 2018)
AbstractThis research aims to find out strategies that can be used to accelerate the pace of economic development in Gunungwungkal sub-district, by referring to physical, environmental, social and local wisdom conditions in Gunungwungkal in 2015. The result is that Gunungwungkal is a plateau with good physical conditions for agriculture and livestock but is constrained by the addition of added value in the production of goods. The number of residents of the productive age is more than the age of being unproductive, but the educational facilities are not sufficient, so other institutions such as training centers are needed. There is tourism potential such as Grojogan Sewu waterfall and monastery, but the infrastructure does not support it. Therefore, the right strategy to accelerate the development of the Gunungwungkal area is to increase the ability and knowledge of the population in order to provide added value to the production results and improve infrastructure, and this cannot be done except with good cooperation between the government and the community.